Motives and markets in health care - Hausman, D (Oxford Uehiro Centre for Practical Ethics, 2013)
The truth about health care policy lies between two exaggerated views: a market view in which individuals purchase their own health care from profit maximizing health-care firms and a control view in which costs are controlled by regulations limiting which treatments health insurance will pay for. This essay suggests a way to avoid on the one hand the suffering, unfairness, and abandonment of solidarity entailed by the market view and, on the other hand, to diminish the inflexibility and inefficiency of the control view. It suggests that the way to mitigate these problems is to recognize the malleability of motivation and the range of factors, in addition to financial incentives, that may influence the behavior of patients and especially physicians.